Increasing the Effectiveness of Preshipment Inspection Services - Dutz, Mark (World Bank, Washington, DC, 2012)
Preshipment inspection can help control overinvoicing or underinvoicing of imports, misclassification of imports, and misappropriation of donor funds provided for import support. Of the various objectives for customs reform, trade facilitation is arguably the most important for efficiency and growth. Because of the potential long-term gains from reform, governments should focus on implementing an effective program for customs modernization and institutional reform, and not view preshipment inspection services as a substitute for this effort. This Note reviews recent evidence on the effectiveness of preshipment inspection services.